Kidney microRNA Expression Pattern in Type 2 Diabetic Nephropathy in BTBR Ob/Ob Mice - Opazo-Ríos, Lucas; Tejera-Muñoz, Antonio; Soto Catalan, Manuel; Marchant, Vanessa; Lavoz, Carolina; Mas Fontao, Sebastián; Moreno, Juan Antonio; Fierro Fernandez, Marta; Ramos, Ricardo; Suarez-Alvarez, Beatriz; López-Larrea, Carlos; Ruiz-Ortega, Marta; et al. (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is the main leading cause of chronic kidney disease worldwide. Although remarkable therapeutic advances have been made during the last few years, there still exists a high residual risk of disease progression to end-stage renal failure. In order to further understand the pathogenesis of tissue injury in this disease, by means of the Next Generation Sequencing we have studied the miRNA differential expression pattern in kidneys of Black and Tan BRachyury (BTBR) ob/ob (leptin deficiency mutation) mouse. This experimental model of T2D and obesity recapitulates the key histopathological features described in advanced human DN and therefore can provide potential useful translational information. The miRNA-seq analysis, performed in the renal cortex of 22-week-old BTBR ob/ob mice, pointed out a set of 99 miRNA significantly increased compared to non-diabetic, non-obese control mice of the same age, while none miRNAs were found significantly decreased. Among them, miR-802, miR-34a, miR-132, miR-101a and mir-379 were the most upregulated ones in diabetic kidneys. The in-silico prediction of potential targets for the 99 miRNAs highlighted inflammatory and immune processes, as the most relevant pathways, emphasizing the importance of inflammation in the pathogenesis of kidney damage associated to diabetes. Other identified top canonical pathways were adipogenesis (related with ectopic fatty accumulation), necroptosis (an inflammatory and regulated form of cell death) and epithelial to mesenchymal transition, the latter supporting the importance of tubular cell phenotype changes in the pathogenesis of DN. These findings will help to understand this complex disease and open new avenues to design therapeutic approaches to DN